Did the Anatolian Hatayis hear of Shah Ismail? (Journal of Alevism-Bektashism Studies, 2024)
Despite the relatively short lifespan of Safavid Shah and Sheikh Ismail (d. 1524), his influence has endured for centuries. While Shah Ismail emerged as one of the most powerful figures in the region during the early 16th century, his political influence began to wane shortly after the Battle of Chaldiran. However, his religious-mystical persona, known under the pen name Hatayi, has retained its vitality for five centuries, particularly in Anatolia. While Ottoman officials and intellectuals ignored Shah Ismail for political reasons for a long time, the greatest factor in maintaining his religious authority was undoubtedly the Anatolian Qizilbash and the poets they raised under the pen name Hatayi. The Anatolian Qizilbash created texts and melodies around the name Hatayi, placing them at the core of their rituals to sustain their religious and cultural identity. Therefore, Shah Ismail Hatayi became immortal through the poems written and sung by the Anatolian Hatayis. The relationship between Shah Ismail and the Anatolian Hatayis, traceable more through narratives and oral culture than reliable documents and records, holds greater significance than the mere reproduction of literary texts or the incorporation of a charismatic leader into the cult of saints by his followers. This relationship conceals the codes of a sociological rupture with political effects that have persisted to this day. Hence, one of the most important grounds for tracing the historical background of the Anatolian Qizilbash faith, an enduring and frequently debated topic, is the relationship between the Anatolian Hatayis and Shah Ismail. We lack sufficient scientific data to determine which of Shah Ismail’s poems circulated in Anatolia before and after 1514, or how many of these have diverged from the tradition or transformed over the past five centuries. In other words, providing an answer to this question based solely on the unique poems and words of Shah Ismail within the ritual universe of contemporary Anatolian Qizilbashism would not contribute comprehensively to understanding the process. At this point, a realistic and accurate first step toward broader and more coherent research could begin with a question previously raised by other scholars: “How and to what extent did the Anatolian Hatayis understand Shah Ismail, and how well do they represent his theological identity?” This article aims to outline Shah Ismail’s theological profile and trace its reflections among the Anatolian Hatayis. First, the historical processes considered crucial in shaping Shah Ismail’s spiritual world are summarized. Subsequently, based on the comparative Hatayi Divanı published in 2017, concepts believed to hold distinctive significance in his theological stance—such as God, Prophet, Sect, Qizilbash, Ja’fari, Husayni, Mawali, and Ali—are analyzed, and their representations among the Anatolian Hatayis are explored.